Seni visual dalam konteks gejala sosial di Malaysia: interpretasi simbolik pada karya catan Fawwaz Sukri Visual art in the context of social Problem’s in Malaysia: symbolic interpretation of Fawwaz Sukri's paintings - Issarezal Ismail; Humin Jusilin (2020)
Contemporary visual art today reflects various phenomena or situations that occur in society and culture in which the visual artwork was created. This study aims to investigate, understand and explain the visual artwork of Fawwaz Sukri in the context of social problems that cover aspects of symbol and meaning. A qualitative approach that emphasize on a system of descriptive, holistic, detailed and in-depth explanatory systems is used in conjunction with a symbolic interpretive approach that serves as an analytical tool to interpret the symbolic meaning of visual art based on various data sources such as observation, interview and documents. Findings of this study have shown that Fawwaz Sukri’s artworks reflects various issues of social problems such as incest, free lifestyle, abortion and prostitution. All this issue was expressed through the application of symbols and signs that come from the Malay culture, popular culture and personal experience in which all of them convey symbolic understanding of the diversity of meanings and messages laden with loads of social criticism and humanity.